2006
DOI: 10.1124/dmd.105.009118
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cryopreserved Human Hepatocytes in Sandwich Culture to Measure Hepatobiliary Transport

Abstract: ABSTRACT:Fresh hepatocytes cultured in a sandwich configuration allow for the development of intact bile canaliculi and the ability to measure hepatic uptake and biliary clearance. A disadvantage of this model is its dependence upon hepatocytes from fresh tissue. Therefore, the ability to use cryopreserved human hepatocytes in this model would be a great advantage. Multiple variables were tested, and the recommended conditions for culturing cryopreserved human hepatocytes in a sandwich configuration in 24-well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
2
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(148 citation statements)
references
References 14 publications
6
139
2
1
Order By: Relevance
“…We have previously shown that SCHH possess significant OATP activity (Bi et al, 2006), and a previous study showed that OATP1B1 and OATP1B3 protein levels are well maintained on day 6 in SCHH (Hoffmaster et al, 2004). Our data show that the uptake clearance of digoxin in sandwich culture is similar to that observed in noncultured hepatocyte suspension, and OATP1B3-specific activity (as measured by CCK-8 uptake clearance) is appreciable in sandwich culture.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…We have previously shown that SCHH possess significant OATP activity (Bi et al, 2006), and a previous study showed that OATP1B1 and OATP1B3 protein levels are well maintained on day 6 in SCHH (Hoffmaster et al, 2004). Our data show that the uptake clearance of digoxin in sandwich culture is similar to that observed in noncultured hepatocyte suspension, and OATP1B3-specific activity (as measured by CCK-8 uptake clearance) is appreciable in sandwich culture.…”
Section: Discussionsupporting
confidence: 69%
“…We previously reported the ability to use cryopreserved human hepatocytes in sandwich culture (Bi et al, 2006) and have shown that uptake and efflux transporter activities are similar to those in fresh hepatocytes. The purpose of this study was to investigate the hepatic uptake of digoxin using cryopreserved human hepatocytes in sandwich culture.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 5-fold variability was also observed for the uptake of estradiol-17␤-D-glucuronide in suspended human hepatocytes and sandwich-cultured human hepatocytes prepared from cryopreserved human hepatocytes (Shitara et al, 2003;Bi et al, 2006). Multiple OATPs are involved in the hepatic uptake of these ARBs and statins (Nakagomi-Hagihara et al, 2006;Yamashiro et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…at ASPET Journals on May 12, 2018 dmd.aspetjournals.org Downloaded from Bi et al (2006) reported that sandwich-cultured human hepatocytes prepared from cryopreserved human hepatocytes form intact bile canalicular networks and exhibit functional uptake and transportermediated excretion. Use of cryopreserved human hepatocytes would be more convenient than isolating and preparing sandwich-cultured human hepatocytes from fresh human liver.…”
Section: Biliary Clearance Prediction Of Arbs and Statins In Humansmentioning
confidence: 99%
See 1 more Smart Citation